Development of chocolate coated-macapuno (Cocos nucifera Linn.) - Ramirez, Liza Cruz; Francisco, Ma. Leonora dL. (1996.)
The study was conducted to develop an acceptable chocolate-coated macapuno. In Phase I, sensory evaluation was done non four samples with varying levels of macapuno and buco fillings: 50% macapuno-50% buco, 30% macapuno-70% buco, 15% macapuno-85% buco, and 0% macapuno-100% buco. The samples were evaluated in terms of their macapuno flavor, sweetness, mouthfeel, and general acceptability. The results which were analyzed statistically showed 30% macapuno-70% buco as the optimum proportion for the formulation of chocolate-coated macapuno. Standardization and determination of proximate composition was done on the optimum formulation in Phase II. The product was found to have 31.08% moisture, 15.42% fat, 0.53% protein, 1.51% fiber, 1.82% ash, and 49.64% carbohydrates. In Phase III, cost analysis was done on the product to determine the cost of production. Chocolate-coated macapuno costs about P0.405 per piece.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Snack foods; Macapuno